Assessment of Operational Performance of Unsignalized Intersection using Microsimulation: A Case Study of Intersection at Pepsicola, Kathmandu - Budhathoki, Sanjeev; Shrestha, Pradeep Kumar (International Journal on Engineering Technology and Infrastructure Development, 2024)
The intersection at Pepsicola, Kathmandu is a three legged unsignalized intersection. Three approach roads from Jadibuti, Kadaghari and Sanothimi merge at Pepsicola, Kathmandu to form the intersection. The study aims to assess the existing operational scenario of the intersection. The data collected is used to replicate the actual condition of the intersection in PTV VISSIM 2023 after sufficient calibration and validation. VISSIM was preferred over other simulation softwares due to its easiness in use and flexibility. The performance of the intersection is evaluated in terms of Level of Service and Queue length. During the peak hour i.e. 9:00 AM to 10:00 AM the intersection accommodates 3759 vehicular traffic and during the same hour the intersection serves 318 pedestrians. At present condition the Level of Service of the intersection is C with average total delay of 18.62 Sec.